A study on body movement analysis by the foot slip pattern in a fall - Seong, Hyun Kim; Han, Yeong Oh; Dong, Wook Kim (Universiti Kebangsaan Malaysia, 2015)
A fracture, which mostly results from a fall, is fatal for the elderly. A fall occurred when a person cannot maintain the body position. Most falls occurred when a person walks on a slippery surface or trips over an object on the ground during a gait. Most people try to avoid falls instinctively and fall when their attempt fails. As such, this study investigated the difference between two movements- a movement to avoid falls and a forward-falling movement without a fall-avoiding movement- by analyzing the body movements of the subjects. A fast-moving fall-guiding device with a pneumatic actuator was used to guide falls. The movement of the device could simulate a foot slip that may happen during daily activities. A three-axis acceleration sensor and a Bluetooth module were used to avoid disturbing the body movement during a fall as a wire sensor or a movement analysis system does.